Analysis of the silicone polymer surface aging profile with laser-induced breakdown spectroscopy. (19th September 2017) - Wang, Xilin; Hong, Xiao; Wang, Han; Chen, Can; Zhao, Chenlong; Jia, Zhidong; Wang, Liming; Zou, Lin
Abstract: Silicone rubber composite materials have been widely used in high voltage transmission lines for anti-pollution flashover. The aging surface of silicone rubber materials decreases service properties, causing loss of the anti-pollution ability. In this paper, as an analysis method requiring no sample preparation that is able to be conducted on site and suitable for nearly all types of materials, laser-induced breakdown spectroscopy (LIBS) was used for the analysis of newly prepared and aging (out of service) silicone rubber composites. With scanning electron microscopy (SEM) and hydrophobicity test, LIBS was proven to be nearly non-destructive for silicone rubber. Under the same LIBS testing parameters, a linear relationship was observed between ablation depth and laser pulses number. With the emission spectra, all types of elements and their distribution in samples along the depth direction from the surface to the inner part were acquired and verified with EDS results. This research showed that LIBS was suitable to detect the aging layer depth and element distribution of the silicone rubber surface.